Toward understanding the redox properties of model chromophores from the greenfluorescent protein family: an interplay between conjugation, resonance stabilization, and solvent effects - Ghosh, Debashree; Acharya, Atanu; Tiwari, Subodh C.; Krylov, Anna I. (Journal of Physical Chemistry B, 2012)
The redox properties of model chromophores from the green fluorescent protein family are characterized computationally using density functional theory with a long-range corrected functional, the equation-of-motion coupled-cluster method, and implicit solvation models. The analysis of electron-donating abilities of the chromophores reveals an intricate interplay between the size of the chromophore, conjugation, resonance stabilization, presence of heteroatoms, and solvent effects. Our best estimates of the gas-phase vertical/adiabatic detachment energies of the deprotonated (i.e., anionic) model red, green, and blue chromophores are 3.27/3.15, 2.79/2.67, and 2.75/2.35 eV, respectively. Vertical/adiabatic ionization energies of the respective protonated (i.e., neutral) species are 7.64/7.35, 7.38/7.15, and 7.70/7.32 eV, respectively. The standard reduction potentials (E-red(0)) of the anionic (Chr(center dot)/Chr(-)) and neutral (Chr(+center dot)/Chr) model chromophores in acetonitrile are 0.34/1.40 V (red), 0.22/1.24 V (green), and -0.12/1.02 V (blue), suggesting, counterintuitively, that the red chromophore is more difficult to oxidize than the green and blue ones (in both neutral and deprotonated forms). The respective redox potentials in water follow a similar trend but are more positive than the acetonitrile values.

Extension of the effective fragment potential method to macromolecules - Gurunathan, Pradeep Kumar; Acharya, Atanu; Ghosh, Debashree; Kosenkov, Dmytro; Kaliman, Ilya; Shao, Yihan; Krylov, Anna I.; Slipchenko, Lyudmila V. (Journal of Physical Chemistry B, 2016)
The effective fragment potential (EFP) approach, which can be described as a nonempirical polarizable force field, affords an accurate first-principles treatment of noncovalent interactions in extended systems. EFP can also describe the effect of the environment on the electronic properties (e.g., electronic excitation energies and ionization and electron-attachment energies) of a subsystem via the QM/EFP (quantum mechanics/EFP) polarizable embedding scheme. The original formulation of the method assumes that the system can be separated, without breaking covalent bonds, into closed-shell fragments, such as solvent and solute molecules. Here, we present an extension of the EFP method to macromolecules (mEFP). Several schemes for breaking a large molecule into small fragments described by EFP are presented and benchmarked. We focus on the electronic properties of molecules embedded into a protein environment and consider ionization, electron-attachment, and excitation energies (single-point calculations only). The model systems include chromophores of green and red fluorescent proteins surrounded by several nearby amino acid residues and phenolate bound to the T4 lysozyme. All mEFP schemes show robust performance and accurately reproduce the reference full QM calculations. For further applications of mEFP, we recommend either the scheme in which the peptide is cut along the C-alpha-C bond, giving rise to one fragment per amino acid, or the scheme with two cuts per amino acid, along the C-alpha-C and C-alpha-N bonds. While using these fragmentation schemes, the errors in solvatochromic shifts in electronic energy differences (excitation, ionization, electron detachment, or electron-attachment) do not exceed 0.1 eV. The largest error of QM/mEFP against QM/EFP (no fragmentation of the EFP part) is 0.06 eV (in most cases, the errors are 0.01-0.02 eV). The errors in the QM/molecular mechanics calculations with standard point charges can be as large as 0.3 eV.